Stemming the flow : abuses against migrants, asylum seekers and refugees. Vol. 3 (Human Rights Watch New YorkUS, 2006)
Addresses the treatment of sub-Saharan Africans in the Libyan criminal justice system. Looks at the migration and asylum policies of the EU, which is cooperating with Libya on migration control without prioritising protection.
Keywords: MIGRANTS